Improving the clinical-care pathway of an ayurvedic hospital : a teaching case for developing process improvement capabilities - Bandara, Wasana; Thennakoon, Dharshani; Syed, Rehan; Mathiesen, Paul; Ranaweera, K. K. D. S. (London : Palgrave MacMillan UK, 2016)
Business Process Management (BPM) is a topic that has received immense attention in information systems research and practice. While its adoption has been increasing rapidly, many companies struggle to find BPM professionals with the appropriate skills, hence BPM education has been an area of increasing interest as well. One big challenge for BPM education is the lack of teaching resources. Appropriately written BPM teaching cases derived from real-life case scenarios has been recognised as a valuable means to address this gap. Yet, teaching cases that are rich in context dedicated to BPM are still scarce. This teaching case, specifically developed for business process improvement education purposes, is designed as a rich resource to address this gap. Teaching notes with an extensive set of multimedia ancillary material are also available to instructors upon request. This case study is based on a real-life patient-care process of a national Ayurvedic hospital in Sri Lanka. With its position as the leading national institute for Ayurvedic research and teaching, the hospital has the potential to make striding impacts with Ayurvedic innovations both nationally and globally. This narrative describes the current patient-care process in detail, challenging students to analyse the current process and derive justifiable high-impact creative/innovative recommendations that are feasible to the case's context and improve business processes at the hospital.
Originally Published InBandara, W., Thennakoon, D., Syed, R., Malthiesen, P., & Ranaweera K. K. D. S. (2016). Improving the clinical-care pathway of an Ayurvedic hospital: a teaching case for developing process improvement capabilities. Journal of Information Technology Teaching Cases, 6, 111-120. London, UK: Palgrave Macmillan.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Medicine, Ayurvedic -- Sri Lanka -- Case studies; Hospitals -- Administration -- Sri Lanka -- Case studies; Health services administration -- Sri Lanka -- Case studies; Organizational change -- Management -- Case studies